The acetyltransferase activity of CBP stimulates transcription. - Martinez-Balbás, M A (1998)
The CBP co-activator protein possesses an intrinsic acetyltransferase (AT) activity capable of acetylating nucleosomal histones, as well as other proteins such as the transcription factors TFIIE and TFIIF. In addition, CBP associates with two other TSs, P/CAF and SRC1. We set out to establish whether the intrinsic AT activity of CBP contributes to transcriptional activation. We show that a region of CBP, encompassing the previously defined histone AT (HAT) domain, can stimulate transcription when tethered to a promoter. The stimulatory effect of this activation domain shows some promoter preference and is dependent on AT activity. Analysis of 14 point mutations reveals a direct correlation between CBP's ability to acetylate histones in vitro and to activate transcription in vivo. We also find that the HAT domains of CBP and P/CAF share sequence similarity. Four conserved motifs are identified, three of which are analogous to motifs A, B and D, found in other N-acetyltransferases. The fourth motif, termed E, is unique to CBP and P/CAF. Mutagenesis shows that all four motifs in CBP contribute to its HAT activity in vitro and its ability to activate transcription in vivo. These results demonstrate that the AT activity of CBP is directly involved in stimulating gene transcription. The identification of specific HAT domain motifs, conserved between CBP and P/CAF, should facilitate the identification of other members of this AT family.